Traces of the Hidden: Ungraspable ALICE (EAAE Annual Conference Proceedings, 2019)
What we call visible is (…) the surface of a depth, a cross section upon a massive being. — Maurice Merleau-PontyIf, as stated by the French philosopher Guillaume Blanc [2], the visible is sewn to the invisible, while reading the projects developed by students, we should be able to read traces of the hidden, the structure which made them possible. We will therefore focus on HOUSE 1, an experimental collaborative project designed and built by 227 first-year architecture students by the end of the spring semester 2016 in the XXX university campus.
Keywords: Merleau-Ponty; ProtoStructure; prefabrication; collaboration